Five-year (2013–2017) trends in the incidence and prevalence of musculoskeletal system diseases among the adult population of Russia - R. M. Balabanova; T. V. Dubinina (Современная ревматология)
Objective: to analyze trends in the incidence and prevalence of major rheumatic diseases (RDs) among the adult population of Russia in 2013 to 2017.Material and methods. The trends in the incidence and prevalence of major RDs were analyzed among the adult population of Russia over 5 years (in 2013 to 2017) according to the statistical reports of the Ministry of Health of Russia, which are based on the data of accounting form No. 12 “Information on the number of diseases recorded in patients living in the region served by a health care facility”. The analysis was carried out in eight Federal Districts (FDs).Results and discussion. Over 5 years, there was a slight increase in the number of patients (by 21,677) with musculoskeletal diseases (MSDs) among the adult population of Russia and a small (0.64%) decrease in their prevalence. Noninflammatory osteoarticular diseases, such as osteopathy, chondropathy, deforming dorsopathies, and arthropathies (74%), were leading among MSDs. The incidence of osteoarthritis (OA) was highest: more than 4 million people, which is a quarter of all RDs. The increase in the number of patients with OA was observed annually, but was insignificant for 5 years – 190.400 people; the prevalence of OA increased by 3.7%. The largest number of patients with OA was registered in the Central (1.1 million) and Volga (0.9 million) FDs.The incidence of rheumatoid arthritis (RA) increased insignificantly in the Central, Northwestern, Southern, Ural, and Siberian FDs and decreased in the Volga and Far Eastern FDs. There was a substantial (21%) decrease in the prevalence of RA in the North Caucasian FD. There was a significant increase in both the incidence and prevalence of spondylopathy (SP) in almost all FDs, except for the Volga FD. In contrast, these indicators for reactive arthritis (ReA) had decreased in five FDs by 2017 and slightly increased in three FDs. These indicators fluctuated in almost all FDs for 5 years.The incidence and prevalence of psoriatic arthritis (PsA) showed a annual increase particular in the North Caucasian FD by 29%. The incidence of PsA slightly decreased only in the Siberian FD. The number of patients with systemic connective tissue diseases (SCTD) increased insignificantly in all FDs, with the exception of the North Caucasian FD, in which the prevalence of SCTD reduced dramatically (by 42%). The incidence of osteoporosis (OP) fluctuated during 5 years; by 2017, there had been its rise in five FDs, especially in the Northwestern FD. The prevalence of OP was found to increase significantly (by 33.5%) in the North Caucasian FD.Evaluation of the age composition of patients showed that OA and OP were more common in the older age group; and ReA; SP and SCTD were in the younger age one. There were no differences in the age composition of patients with RA.Conclusion. The analysis of the statistical incidence and prevalence rates of RDs in the adult population of Russia suggests that there is an increase in the number of patients with this pathology throughout the country.